Alcoholism, Work, and Income - Mullahy, John; Sindelar, Jody L. (Journal of Labor Economics, 1993)
This article reports on an empirical analysis of the relationships between alcoholism and income and working. We show that the relationships between alcoholism and labor market success have important age or life-cycle dimensions. We present evidence that alcoholism may affect income more by restricting labor market participation than by affecting the wages of workers. Finally, we demonstrate that the effects of alcoholism on earnings depend on the extent to which one controls for other covariates associated with alcoholism; as such, we suggest that there may be important indirect as well as direct effects of alcoholism on labor market success.